Prevalence and Factors Associated with COVID-19 Vaccine Acceptance among Adult Population in Northern Uganda. A Cross-Sectional Study (London Journal of Medical and Health Research, 2023)
Background:  When COVID-19 vaccines arrived in Uganda in March of 2021, there was inadequate information on vaccine acceptance in the population due to many factors, but mainlydue to misinformation and disinformation circulating in Ugandan media. This study aimed to determine the prevalence and factors associated with COVID-19 vaccine acceptance among adult population in northern Uganda.Methods: We conducted a cross-sectional study on 723-adult populations in northern Uganda from March to April of 2022. Participants were selected by systematic sampling from twenty-four health facilities in Acholi sub-region. SPSS version 25.0 was used for data analysis at multivariable regression analysis and a p-value
Keywords: COVID-19 vaccine; acceptance; prevalence; Village health teams (VHTs)